The Roles of NRF2 in Modulating Cellular Iron Homeostasis - Kerins, Michael John; Ooi, Aikseng (Antioxidants & redox signaling, 2018)
Iron and oxygen are intimately linked: iron is an essential nutrient utilized as a cofactor in enzymes for oxygen transport, oxidative phosphorylation, and metabolite oxidation. However, excess labile iron facilitates the formation of oxygen-derived free radicals capable of damaging biomolecules. Therefore, biological utilization of iron is a tightly regulated process. The nuclear factor (erythroid-derived 2)-like 2 (NRF2) transcription factor, which can respond to oxidative and electrophilic stress, regulates several genes involved in iron metabolism. Recent Advances: The bulk of NRF2 transcription factor research has focused on its roles in detoxification and cancer prevention. Recent works have identified that several genes involved in heme synthesis, hemoglobin catabolism, iron storage, and iron export are under the control of NRF2. Constitutive NRF2 activation and subsequent deregulation of iron metabolism have been implicated in cancer development: NRF2-mediated upregulation of the iron storage protein ferritin or heme oxygenase 1 can lead to enhanced proliferation and therapy resistance. Of note, NRF2 activation and alterations to iron signaling in cancers may hinder efforts to induce the iron-dependent cell death process known as ferroptosis. Despite growing recognition of NRF2 as a modulator of iron signaling, exactly how iron metabolism is altered due to NRF2 activation in normal physiology and in pathologic conditions remains imprecise; moreover, the roles of NRF2-mediated iron signaling changes in disease progression are only beginning to be uncovered. Further studies are necessary to connect NRF2 activation with physiological and pathological changes to iron signaling and oxidative stress. Antioxid. Redox Signal. 00, 000-000.